Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2166/hydro.2015.140
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate data mining for estimating the rate of discolouration material accumulation in drinking water distribution systems

Abstract: Particulate material accumulates over time as cohesive layers on internal pipeline surfaces in water distribution systems (WDS). When mobilised, this material can cause discolouration. This paper explores factors expected to be involved in this accumulation process. Two complementary machine learning methodologies are applied to significant amounts of real world field data from both a qualitative and a quantitative perspective. First, Kohonen self-organising maps were used for integrative and interpretative mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…A key finding from the analysis is that the risk for water quality stagnation appears to be associated with high water age. SOMs have also been used to explore the factors contributing to higher material accumulation rates in water distribution pipeline systems [2].…”
Section: Som Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A key finding from the analysis is that the risk for water quality stagnation appears to be associated with high water age. SOMs have also been used to explore the factors contributing to higher material accumulation rates in water distribution pipeline systems [2].…”
Section: Som Analysismentioning
confidence: 99%
“…Many of these are kinetic in nature and hence residence time within a system (or water age) may be an indicator of such deterioration [1]. It has also been shown that higher water temperatures may enhance water quality deterioration [2][3][4][5][6]. Many of the chemical changes that influence water quality are driven by reaction kinetics which are temperature dependent, and temperature also influences microbial populations [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible using the developed game to manipulate pumps, valves and other system components in a similar fashion. Similarly, the game engine allows other type of WDS problems to be analysed, such as water quality issues [43], pump operations [44], leakage [45,46] and calibration [47], according to the needs of the game.…”
Section: A Serious Game For Wds Analysis Design and Evaluation: Segwadementioning
confidence: 99%
“…Field measurements from an extensive and prolonged program of cleaning actions that covers ∼ 450 km of pipes per year by Dutch water company PWN indicate that highturbidity events often occur in repeatable spatial and temporal patterns (Blokker and Schaap, 2011;Mounce et al, 2016). Factors that influence these patterns include the hydraulic vigor associated with the buildup and displacement of particles and sediment load from the treatment plant and transport mains upstream from the DWDS (Blokker and Schaap, 2015a).…”
Section: Introductionmentioning
confidence: 99%